Faktor-Faktor yang Mempengaruhi Efektivitas Sistem Informasi Akuntansi pada PT Pegadaian di Kabupaten Klaten - Ningtyas, Kurnia Puspita; Wijayanti, Anita; Astungkara, Agni (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study aims to examine the influence of variables of information technology sophistication, level of education, skill, knowledge of accounting department employees, and participation of accounting information system users on the effectiveness of accounting information systems. This research method uses a quantitative descriptive approach and sampling in this study is purposive sampling. Data collection techniques were obtained through surveys using questionnaires distributed to 40 employee respondents who used accounting information systems at PT. Pegadaian Klaten Branch. The data analysis used in this study was multiple regression analysis using SPSS Version 26. The results of this study prove that the sophistication of information technology has a significant effect on the effectiveness of accounting information systems, the level of education does not have a significant effect on the effectiveness of accounting information systems, skill has a significant effect on the effectiveness of accounting information systems, knowledge of accounting employees has a significant effect on the effectiveness of accounting information systems, and the participation of accounting information systems has an effect significant to the effectiveness of accounting information systems.